Coherent control of two-color above-threshold photoemission from tungsten nanotips - Paschen, Timo; Förster, Michael; Krüger, Michael; Lemell, Christoph O; Wachter, G.; Libisch, Florian; Madlener, T.; Burgdorfer, J.; Hommelhoff, Peter (Journal of Physics: Conference Series, 2017)
Synopsis We demonstrate coherently controlled two-color above-threshold photoemission from a single crystal tungsten nanotip. With optimized fundamental and second harmonic intensities near perfect phase contrast can be obtained.
CRIS-Team Scopus Importer:2022-06-05